Métodos de gestão da qualidade e de processos no setor logístico: um estudo multicaso com operadores logísticos na Região Metropolitana de Salvador - SANTOS, Jonatas de Araújo (2014)
This study deals with quality management initiatives and redesign process that was done in the logistics of the metropolitan region of Salvador companies in the period 2009 to 2013 Through a sample of five companies, documentary research was conducted, as well as the application questionnaires and interview guide with employees of companies and their executives accountable. The paper presents an analysis of the logistics activities of each company studied, seeking to highlight the key managerial methods for improving or changing processes used in operations, such as: continuous improvement, kaizen and reengineering. Throughout the work, the gains of quality management initiatives and redesign of processes adopted and operating results for the past five years are identified. The paper addresses the perception of employees, the characteristics of the local market and methodologies for managing operational processes. Mostly, it was found that the surveyed companies seeking motivation of its teams, customer loyalty and productivity gains with the adoption of managerial methods processes. Finally, the present study found the positive results achieved by logistics companies, with the use of management methods in its operational processes.